Urinary monohydroxylated polycyclic aromatic hydrocarbons in primiparas from Shenzhen, South China: Levels, risk factors, and oxidative stress. (April 2020) - Peng, Mengmeng; Lu, Shaoyou; Yu, Yingxin; Liu, Shan; Zhao, Yang; Li, Chun; Ma, Shengtao
Abstract: The main objectives of the present study were to investigate urinary monohydroxylated polycyclic aromatic hydrocarbons (OH-PAHs) in 77 primiparas who live in Shenzhen, Guangdong Province, China, and their association with 8-hydroxy-2′-deoxyguanosine (8-OHdG) and human health risks. High detection frequencies of OH-PAHs demonstrated the wide occurrence of chemicals in the human exposure to PAHs. The urinary concentrations of Σ7 OH-PAHs ranged from 1.37 to 45.5 ng/mL, and the median concentrations of 1-hydroxynaphthalene (1-OHN), 2-hydroxynaphthalene (2-OHN), 2-hydoxyfluorene (2-OHF), ΣOHPhe (the sum of 1-, 2+ 3-hydroxyphenanthrene), and 1-hydroxypyrene (1-OHP) were 3.00, 2.58, 0.31, 0.44, and 0.51 ng/mL, respectively. In the sum concentration of seven OH-PAHs, 1-OHN accounted for the largest proportion (43.7% of Σ7 OH-PAHs), followed by 2-OHN (37.1%), 2-OHF (4.94%), 1-OHP (8.01%), 1-OHPhe (4.79%), and 2+3-OHPhe (1.46%). The present results showed that vehicle exhaust and petrochemical emission are the main sources of PAHs in primiparas in Shenzhen, and inhalation is the most important exposure route. The living conditions have a significant influence on human exposure to PAHs. The concentrations of 8-OHdG were positively correlated with OH-PAH concentrations in urine because evidence suggested that urinary 8-OHdG levels can be considered as a biomarker of oxidative DNA damage. Hazard quotient was used to assess the human health risks from exposure to single compound, and hazard index was used to assess the cumulative risks of the compounds, which demonstrated that the exposure risks from PAHs in primiparas were relatively low. Graphical abstract: Image 1 Highlights: Urinary OH-PAHs were measured in primiparas in Shenzhen China. 1-OHN and 2-OHN were predominant components among the seven OH-PAHs. Household annual income has an influence on OH-PAHs in the urine of primiparas. A dose-dependent increase in urinary levels of 8-OHdG with OH-PAHs was found. Abstract : Urinary monohydroxylated polycyclic aromatic hydrocarbons and risk factor study from primiparas can provide useful information on potential health risks for fetuses.